Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) on UM-PTKIN Questions on Islamic Religious Education Materials - Mispani Mispani; M. Sayyidul Abrori; Umar Alfaruq A Hasyim; Kushendar Kushendar; Muslimah Muslimah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This article focused on discussing Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) on the UM-PTKIN (Ujian Masuk Perguruan Tinggi Keagamaan Islam Negeri) Islamic Religious Education Material. It is case prospective students in higher education must be able to think at a higher level (High Order Thinking Skills, HOTS) such as analytical skills, evaluation skills and material creation skills. The method used Prisma Protocl namely identification, screening, eligibility, and inclusion (Alias et al., 2018). Therefore, the provision of college entrance examination tests is an important element in selecting prospective students. The results of this study indicate that the items for the UM-PTKIN PAI material are in the HOTS category and low oeder thinking skills (LOTS). The material for Akidah Akhlak became the largest contributor and Al-Quran Hadith as the least contributor to the HOTS category questions. The Islamic Religious Education Study Program (PAI) is a study program that is in great demand and its graduates are highly anticipated to be able to sow an understanding of Islam to answer various social, political, and religious challenges in Indonesia. This article provides recommendations for UM-PTKIN policy makers to be able to increase the number of compositions of HOTS questions in subsequent selections in order to improve the quality of PAI student input in the following periods. Keywords: Higher Order Thinking Skills, Lower Order Thinking Skills, UM-PTKIN Material